Responsibility of Individual Company Shareholders in the Event that an Individual Company Suffers Losses Based on Law Number 11 of 2020 Concerning Job Creation - Rahmadhani, Elsha; Adriaman, Mahlil (Universitas Ibn Khaldun Bogor, 2024)
The purpose of this study is to study, review, and analyze the responsibilities of shareholders in an individual company in the Job Creation Law and related government regulations.. This examination regulates juridical exploration with an approach to legal guidelines that are subsequently taken into account. Primary and secondary legal materials are two types of data sources that make up secondary data. Information collection strategies using library research. Legal analysis techniques are used to review primary and secondary legal materials. The process of thinking using rational reasoning strategies is used to reach decisions, especially points of view sourced from general information and then assess a particular event. The utilitarian hypothesis, the legal certainty hypothesis, and the legal discovery hypothesis are used as scientific tools in surveying this study. Individual Company Shareholders can be held liable up to their personal assets within the limits determined by Law Number 11 of 2020 concerning Job Creation, even though individual Company Shareholders are only responsible for a number of shares they own